Les enjeux des soins palliatifs pédiatriques en milieu hospitalier tertiaire : portrait d’une culture interdisciplinaire porteuse d’espoir - Claude Julie Bourque; Marta Martisella; Marc-Antoine Marquis (Enfances, Familles, Générations, 2023)
Research Framework: In 1999, Montreal’s Sainte-Justine University Hospital created a pediatric palliative care (PPC) service that was gradually deployed in all sectors of the hospital. A retrospective and critical research program aims to understand the evolution of practices and to pinpoint current issues. Objectives: This article presents a portrait of PPC in tertiary care settings in order to fuel reflection on the evolution of practices by identifying research priorities at the clinical, organizational and systemic levels. Methodology: A mixed methods approach is used for this research intervention. An archive database (1999-2021) and workshop proceedings (2021-2022) were subjected to descriptive statistical analysis, conceptual analysis, and collective narration. Results: PPC interventions have increased over the year and then stabilized. The number of requests does not correlate with the number of deaths for a given area. Respondents described 10 central themes for PPC practice, training and research: (1) patient needs at the tertiary hospital setting, (2) pediatric specificities of palliative and end-of-life care, (3) child centredness, (4) pain and suffering or well-being and quality of life, (5) motivations and needs of caregivers, (6) interdisciplinary and interprofessional practices, (7) training and skills, (8) practice norms and indicators, (9) ethical and systemic dimensions of PPC, and (10) hope and high hopes. Conclusion: Conceptual, procedural, and educational tools are essential to improve quality and accessibility of care and PPC services. Contribution: We aim to contribute to the reflection on PPC by describing our perspective and by stimulating interactions among the various hospitals and communities involved.